CZY POTRZEBNI SĄ NAM DZISIAJ HUMANIŚCI? Z BADAŃ HETEROSTEREOTYPU NA PODSTAWIE WYPOWIEDZI STUDENTÓW RÓŻNYCH WYDZIAŁÓW UMCS - Karwatowska, Małgorzata; Siwiec, Adam (Studia Europaea Gnesnensia, 2017)
The aim of the authors is to recreate the heterosterotype of a humanities person through an analysis of notions communicated by students of non-humanities majors. Their task was to explain who a humanities person is, which professions they may practice, which competences are characteristic for people with such backgrounds and what differences may be noted between people who have studied in distinct fields; finally, the respondents were asked to answer whether humanities persons are needed today.